Detection and Analysis of Vibration Noise in a Residence - Xie, Hui; Zhou, Lincong; Zhang, Wei (Journal of Research in Science and Engineering, 2025)
In order to solve the problem of strong local vibration and noise during the operation of a residential water pump, on-site vibration and noise detection was carried out on the building. The vibration response of the building was evaluated according to the relevant norms such as human comfort, the causes of vibration and noise were analysed, and various vibration reduction schemes such as strengthening pump maintenance and rubber vibration .The causes of vibration and noise were analyzed, and various vibration reduction schemes such as strengthening pump maintenance and rubber vibration isolator were proposed according to the vibration characteristics and actual requirements. It provides technical reference for the vibration reduction design of the same type building pump.